A critical approach to SDGs through Collaborative Online International Learning: experiences from Canada and Spain - Campoy-Cubillo, Mari Carmen; Jimenez-Estrada, Vivian (Frontiers in Education, 2025)
IntroductionThe Collaborative Online International Learning (COIL) is described as a pedagogical experience linking the classrooms of two or more higher education institutions across culturally and linguistically differentiated regions. COIL intends to provide academics and students with the ability to communicate and collaborate with peers internationally through online interactions. During the Fall of 2021, this collaboration involved the Universitat Jaume I (UJI), located in the city of Castelló de la Plana in Spain and Algoma University, located on the traditional territory of the Anishinaabek Nation, as well as the homelands of the Métis Nation. The student profiles, each institutions’ geographical locations, as well as the linguistic, cultural and critical approaches to teaching and learning provided ample opportunities and challenges for the development and implementation of this experience.MethodsThe purpose of this paper is to provide a pedagogical reflection on the development of a 5-week module taught together during three academic years. The authors provide an account and reflection of their collaboration centered on the institutional challenges and opportunities that currently exist for courses that aim to engage Indigenous and critical/ecological thinking.Results and discussionThe background of the collaboration leads to a detailed analysis of the context of COIL implementation and the reflections on the modules’ development and improvement. Our recommendations are based on lessons learned from the substantive and technical challenges and opportunities on the complexity of teaching about contemporary ecological/social issues, as well as the tools required to inspire future activists.